Utilizing Film as a Writing Tool in EFL learners - Ardhiansyah, Alvin; Saifulloh, Ahmad Iklil; Mardiana, Wiwik; Ganinda, Nurhayati (PT. Kreasi Karya Majakata, 2024)
Despite the importance of writing skills in education and professional settings, a significant gap exists in effective teaching methods that engage EFL (English as a Foreign Language) learners. This study explores the integration of films as a tool to enhance descriptive writing skills among EFL students. The research employs a descriptive qualitative design, analyzing data from classroom observations and interviews. Findings reveal that films provide visual, sensory, and emotional stimuli, which help students improve their writing by making descriptions more vivid and contextually coherent. The study's implications suggest that using films can bridge the gap between traditional teaching methods and the modern demands of writing proficiency.